A predicted astrometric microlensing event by a nearby white dwarf. (21st April 2018) - McGill, Peter; Smith, Leigh C; Evans, N Wyn; Belokurov, Vasily; Smart, R L
ABSTRACT: We used the Tycho- Gaia Astrometric Solution catalogue, part of Gaia Data Release 1, to search for candidate astrometric microlensing events expected to occur within the remaining lifetime of the Gaia satellite. Our search yielded one promising candidate. We predict that the nearby DQ type white dwarf LAWD 37 (WD 1142-645) will lens a background star and will reach closest approach on 2019 November 11 (±4 d) with impact parameter 380 ± 10 mas. This will produce an apparent maximum deviation of the source position of 2.8 ± 0.1 mas. In the most propitious circumstance, Gaia will be able to determine the mass of LAWD 37 to ${\sim }3\hbox{ per cent}$ . This mass determination will provide an independent check on atmospheric models of white dwarfs with helium rich atmospheres, as well as tests of white dwarf mass radius relationships and evolutionary theory.